DOMINATION DOT-CRITICAL FUZZY GRAPH - HUSSAIN, R. JAHIR; BANU, S. AMEENA (International Journal of Mathematical Archive, 2018)
In general (G) can be made to increase or decrease by the removal of nodes from G. In this paper we discussed the edge contraction (or identifying any two strong adjacent vertices) and domination dot critical fuzzy graph. A fuzzy graph is said to be domination dot critical if contracting any strong edge or identifying any two strong adjacent vertices decreases the fuzzy domination number.